PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP DAN SELF ESTEEM DITINJAU DARI KEMAMPUAN AWAL MATEMATIKA PESERTA DIDIK DI SMP NEGERI KOTA BIMA - Khusnul Syuhada; Suyono Suyono; Eti Dwi Wiraningsih (UIN Sumatera Utara Medan, 2022)
The purpose of this quantitative study is to see the effect of the PBL model on the ability to understand concepts and self-esteem based on the students' initial mathematical abilities. The design of this research is a quasi-experimental with a population of all junior high school students in the Raba sub-district of Bima City for the 2020/2021 academic year. The research subjects were randomly selected, namely students from class VIII-A of SMP 05 Bima and VIII-A of SMP 06 Bima as the experimental class, while class VIII-D of SMP 05 Bima and VIII-C of SMP 06 Bima were the control class. The data collection technique used a test instrument to measure the ability to understand mathematical concepts and a questionnaire to measure students' self-esteem. Data analysis used descriptive statistics in the form of two-way ANOVA and t-test. The average value of students' conceptual understanding skills in the experimental class is 62.00 and the control class is 59.25. Based on data interpretation and t-test analysis with a significance level (α) = 0.05, the value of sig = 0.032 so that sig < . With the results obtained, it is informed that there is an effect of the PBL learning model on the ability to understand mathematical concepts of eighth grade students of SMP in Raba sub-district, Bima City.